Impact of Research About the Early Development of Children With Intellectual Disability: A Science Mapping Analysis - Schuengel, Carlo; van Rest, Maaike M.; Stanford, Catherine E.; Hastings, Richard P. (Frontiers in Education, 2019)
The ‘Warnock Report’ (DfES, 1978) underlined the importance of early intervention for children with a range of special educational needs and the importance of partnership with families. This paper focuses on young children with intellectual disability to describe the longitudinal research on early development that has emerged since the report, and to describe the scholarly literature that has been impacted by this longitudinal work. First, we conducted a systematic literature search for primary reports of longitudinal studies on the early development of children with intellectual disability. Included studies were those that measured dependent (i.e., developmental outcomes) and independent variables (i.e., risk and resilience factors) on at least two measurement occasions (i.e., truly longitudinal), starting before the end of the 7th year of life, with samples including children with intellectual disability (or related terms). The topics of these studies, and of the publications that have cited these longitudinal studies, were extracted from titles and abstracts using machine reading and subjected to multidimensional clustering (VOSviewer; Van Eck & Waltman, 2019). The resulting body of 101 research studies (about 2.5 studies per year) covered a scattering of topics without a dominant focus. The literature that was impacted by these longitudinal studies consisted of 3,491 scientific publications. Three clusters of topics emerged from mapping the terms used in these publications, which were dominated by (1) syndrome and disorder related terms; (2) autism-related terms; and (3) disability and parent related terms. Topics related to autism and, to a lesser extent, parents showed the strongest increase over time. Topics related to intervention and programmes were mostly linked to the topics disability and parents. Taking into account the science mapping as well as features of the context in which research on intellectual disability takes place, we suggest a collaborative research agenda that systematically links topics relevant for intervention with longitudinal research, in co-creation with families.